Brand publics participatory approach via influencers in strategic communications - Tran, Thuy Vu Vi (Kansas State University, 2023)
The study aims to examine current practices, experiences, and expectations of the PR industry regarding the relationship between brands-influencers-audiences in strategic communications through in-depth interviews with professional practitioners. The discussion will then be combined with the suggestions of the literature to introduce a new approach to engaging with the public through corporate communication efforts. The new approach focuses on promoting the customer participatory culture, where brands not only persuade their customers to buy their products, or increase their brand reputation through paid advertising and PR efforts, but also develop genuine two-way relationships with their public, to receive feedback and constructive comments to better serve their customers, using influencers as the facilitator.
Keywords: Strategic communication; Influencer; Participatory culture; Two-way communication; Dialogic communication; Audience engagement